Transitioning home: A four‐stage reintegration hospital discharge program for adolescents hospitalized for eating disorders. Issue 4 (26th June 2015) - Dror, Sima; Kohn, Yoav; Avichezer, Mazal; Sapir, Benjamin; Levy, Sharon; Canetti, Laura; Kianski, Ela; Zisk‐Rony, Rachel Yaffa
Abstract Purpose Treatment for adolescents with eating disorders (ED) is multidimensional and extends after hospitalization. After participating in a four‐step reintegration plan, treatment success including post‐discharge community and social reintegration were examined from perspectives of patients, family members, and healthcare providers. Design and Methods Six pairs of patients and parents, and seven parents without their children were interviewed 2 to 30 months following discharge. Results All but two adolescents were enrolled in, or had completed school. Five worked in addition to school, and three completed army or national service. Twelve were receiving therapeutic care in the community. Practice Implications Adolescents with ED can benefit from a systematic reintegration program, and nurses should incorporate this into care plans.